Acute hyperglycemia increases renal tissue oxygenation as measured by BOLD-MRI in healthy overweight volunteers. (April 2019) - Vakilzadeh, Nima; Zanchi, Anne; Milani, Bastien; Ledoux, Jean-Baptiste; Braconnier, Philippe; Burnier, Michel; Pruijm, Menno
Abstract: Aim: Animal studies have suggested that acute hyperglycemia induces transient renal hypoxia and kidney damage, yet this has not been tested in humans. Therefore, we assessed in human subjects the effect of acute hyperglycemia on renal tissue oxygenation as measured with blood oxygenation level-dependent magnetic resonance imaging (BOLD-MRI). Methods: In this single center prospective interventional study, healthy overweight subjects were recruited. BOLD-MRI was performed before and immediately after the intravenous administration of 0.15 g/kg of glucose in a 20% solution under standard hydration and fasting conditions. R2* maps were analyzed using the twelve layer concentric objects (TLCO) technique, a semi-automatic procedure which divides the kidney parenchyma in 12 equal layers at increasing depth. R2* is a measure of local desoxyhemoglobin concentrations, with high R2* values corresponding to low oxygenation. Results: Nineteen overweight subjects were enrolled (age 37 ± 10 years, BMI 28.9 ± 3 kg/m 2, HbA1c 5.4 ± 0.3%, 57.9% women): 5 were glucose intolerant, none had diabetes. The mean glycemia rose from 4.5 ± 0.3 mmol/l to 9.0 ± 0.9, 8.9 ± 0.7, 7.7 ± 0.6 and 6.8 ± 0.8 mmol/l at respectively 1, 10, 20 and 30 min after IV glucose. Circulating insulin levels quadrupled. The mean R2* values decreased significantly in all kidney layers, irrespective of glucose intolerance. The lower BMI, the larger the decrease in R2*(spearman's r = 0.41, p = 0.035). Conclusion: These data show that acute hyperglycemia decreases the R2* signal in humans, suggesting an acute increase in renal tissue oxygenation. The precise mechanism of this observation remains unknown, and whether this phenomenon also occurs in patients with diabetes needs additional studies.